Dehumanizing Language Against Women in "TOP 3 Reasons Men Are Unsuccessful in Dating 2022!" Podcast: A CDA Approach - Putri, Ghina Alya; Syahriani, Alfi; Akmal, Hilmi; Handayani, Tuty (Lakon : Jurnal Kajian Sastra dan Budaya, 2025)
This study aims to examine how the GBBB “TOP 3 Reasons Men Are Unsuccessful in Dating 2022! (DATING APPS)” podcast criticizes women using dehumanizing language. The research questions are analyse the discursive strategy, the discourse practice and sociocultural practice. This study is a qualitative method, using Norman Fairclough’s Critical Discourse Analysis and SFL by Halliday as the theory. The results found there are 4 data being analysed. The findings are the linguistics features criticize and dehumanizing women. In the discourse practice, a male-focused podcast that often criticizes women. On the sociocultural practice, the discourse forms part of the persistent gendered power relations in Canada, mirroring real-world experiences of exclusion and violence while intersecting with capitalist media in the digital creator economy. The study finds that the GBBB podcast discourse participates in sustaining and legitimizing the objectification and dehumanization of women, mirroring and perpetuating existing gender power imbalances in Canadian society.